2005
DOI: 10.1242/dev.01789
|View full text |Cite
|
Sign up to set email alerts
|

The roles of receptor and ligand endocytosis in regulating Notch signaling

Abstract: Cell-cell signaling is a central process in the formation of multicellular organisms. Notch (N) is the receptor of a conserved signaling pathway that regulates numerous developmental decisions, and the misregulation of N has been linked to various physiological and developmental disorders. The endocytosis of N and its ligands is a key mechanism by which N-mediated cell-cell signaling is developmentally regulated. We review here the recent findings that have highlighted the importance and complexity of this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
286
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(298 citation statements)
references
References 114 publications
(130 reference statements)
10
286
0
2
Order By: Relevance
“…In mammals, the Delta-like and Jagged ligands mature as a result of cleavages by tumor necrosis factor α-converting enzyme-like protease and γ-secretase, and could be released as extracellular soluble forms (38). Furthermore, Notch ligands may also be released extracellularly via secreted vesicles (39). Besides Delta and Jagged family members, CCN3 and MAGPs can function as the Notch ligand, causing dissociation of the Notch1 extracellular domain and activation of the receptor (9).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the Delta-like and Jagged ligands mature as a result of cleavages by tumor necrosis factor α-converting enzyme-like protease and γ-secretase, and could be released as extracellular soluble forms (38). Furthermore, Notch ligands may also be released extracellularly via secreted vesicles (39). Besides Delta and Jagged family members, CCN3 and MAGPs can function as the Notch ligand, causing dissociation of the Notch1 extracellular domain and activation of the receptor (9).…”
Section: Discussionmentioning
confidence: 99%
“…It is often thought that signalling events have specific proteins associated with them and thus the notion of signal transduction pathways as a constellation of proteins dedicated to a signalling event. Recent genetic studies in Drosophila have revealed that an increasing number of proteins involved in intracellular traffic are required for the activity of Notch (reviewed in (Le Borgne et al 2005a)). For example, mutants producing defects on endocytosis, recycling, vesicular sorting and multivesicular body formation present defects on Notch signalling (Poodry 1990, Ramain et al 2001, Thompson et al 2005, Vaccari & Bilder 2005, Jaekel & Klein 2006.…”
Section: Notch Traffickingmentioning
confidence: 99%
“…There is some recent experimental evidence in favour of this model (Nichols et al 2007). Another possibility is that ligand endocytosis is required for ligand post-translational modifications which render the ligand competent for activating Notch signalling activity when recycled back to the plasma membrane (Wang & Struhl 2004, Le Borgne et al 2005a, Wilkin & Baron 2005). The latter model is supported by the fact that Delta lacking its intracellular domain is not able to elicit Notch signalling activity (Sun & Artavanis-Tsakonas 1996, Nichols et al 2007).…”
Section: Ligand Traffickingmentioning
confidence: 99%
“…The discrepancies in our findings may be due to differences in which proliferation of VNC and central brain NBs are regulated. To test whether Notch might be hyperactivated in aurA mutants, we examined the membrane localization of Sanpodo (Spdo), which is required to activate Notch but is inhibited by Numb during GMC and SOP asymmetric divisions (O'Connor-Giles and Skeath 2003;Le Borgne et al 2005). In wild-type interphase larval NBs, Spdo displayed a weak cortical staining and in punctate structures throughout the cytoplasm (100%, n = 38; Fig.…”
Section: The Role Of Notch In Nb Proliferationmentioning
confidence: 99%